About pressure in model of the expanding Universe - Sannikov-Proskuryakov, S.S. (Вопросы атомной науки и техники, 2007)
Closed model of Universe on the earlier stage of its evolution is defined more precisely. It is considered here that after the Big Bang and De Sitter’s (exponential) expanding phase in which the pressure is p=-c²ρc (see [1-3]) the post De Sitter’s stage is beginning. State equation on this stage is written in the form p(R)=-c²ρ(R)A(R), where is some pure geometrical factor. Here this equation is investigated and boundary conditions for it are formulated. Explicit expression for A(R) in the class of almost periodical functions is found, that permits to integrate the conservation law. Outgoing from this we come to the following conclusion: at the post De-Sitter’s stage the configuration space of Universe is the Bohr’s compact. Manifold R on which acceleration is positive Rtt>0 are found. Due to the vibrant character of depending A(R) this manifold may advance far in future that is compatible with observed data. Закрита модель Всесвіту на ранній стадії її розвитку визначена більш точно. Вважається, що після Вели-кого Вибуху й де-сітеровскої стадії, що (експоненціально) розширюється і на якій тиск дорівнює p=-c²ρc (див. [1-3]), починається пост-де-сітеровська стадія. Рівняння стану на цій стадії написано у вигляді p(R)=-c²ρ(R)A(R), де A(R) — якийсь чисто геометричний фактор. Досліджено це рівняння й сформульовані для нього граничні умови. Знайдено явний вираз для A(R) в класі майже періодичних функцій, що дозволяє проінтегрувати закон збереження. Виходячи із цього, приходимо до наступного висновку: на пост-де-сітеровскої стадії конфігураційний простір Всесвіту є компактним за Бором. Знайдено різноманіття R, на якому прискорення є позитивним, Rtt>0. Через вібруючий характер залежності A(R) це різноманіття може простиратися далі в майбутнє, що погоджується із даними спостереження. Закрытая модель Вселенной на ранней стадии ее развития определена более точно. Считается, что после Большого Взрыва и де-ситтеровской (экспоненциально) расширяющейся стадии, на которой давление равно p=-c²ρc (см. [1-3]), начинается пост-де-ситтеровская стадия. Уравнение состояния на этой стадии написано в виде p(R)=-c²ρ(R)A(R), где A(R) – некий чистый геометрический фактор. Исследовано это уравнение и сформулированы для него граничные условия. Найдено явное выражение для A(R) в классе почти периодических функций, что позволяет проинтегрировать закон сохранения. Исходя из этого приходим к следующему выводу: на пост-де-ситтеровской стадии конфигурационное пространство Вселенной является боровски компактным. Найдено многообразие R, на котором ускорение является положительным, Rtt>0. Из-за вибрирующего характера зависимости A(R) это многообразие может простираться дальше в будущее, что согласуется с наблюдаемыми данными.